Resting-state functional connectivity between amygdala and the ventromedial prefrontal cortex following fear reminder predicts fear extinction - Feng, Pan (Soc Cogn Affect Neurosci, 2016)
Investigations of fear conditioning have elucidated the neural mechanisms of fear acquisition, consolidation and extinction, but it is not clear how the neural activation following fear reminder influence the following extinction. To address this question, we measured human brain activity following fear reminder using resting-state functional magnetic resonance imaging, and investigated whether the extinction effect can be predicted by resting-state functional connectivity (RSFC). Behaviorally, we found no significant differences of fear ratings between the reminder group and the no reminder group at the fear acquisition and extinction stages, but spontaneous recovery during re-extinction stage appeared only in the no reminder group. Imaging data showed that functional connectivity between ventromedial prefrontal cortex (vmPFC) and amygdala in the reminder group was greater than that in the no reminder group after fear memory reactivation. More importantly, the functional connectivity between amygdala and vmPFC of the reminder group after fear memory reactivation was positively correlated with extinction effect. These results suggest RSFC between amygdala and the vmPFC following fear reminder can predict fear extinction, which provide important insight into the neural mechanisms of fear memory after fear memory reactivation.